the efficacy of lazarus multimadal therapy on stress decline and enhancing health indices in war affected individuals with osteomyelitis - A. khazraee vijafar; M. JANBOZORGI; A. Alipour (Afarand Scholarly Publishing Institute, 2010)
Introduction: The present essay is intended to study how effective the Multimodal Therapy may be on the reduction of tension and the enhancement of well-being indexes in the war-physically handicapped with osteomyelitis. This research is based on pretest-posttest - a quasi-experiment with control group. Methods & Materials: To this end, 28 subjects with mean of 44 years and 7 months (age group of 30-60) were screened and divided into two groups of 14 each, using the accessible volunteer sampling. The both groups responded to General Health Questionnaire and to Cohen Perceived Stress Scale. Their blood tests were taken. The experimental group received the MT for a period of twelve 90-minute sessions. The entire process was repeated. Results: Studying the results drew upon the covariance analysis and suggested that tension, general health and its sub-scales (depression, anxiety, social malfunction and somatic function) are influenced by the MT. However, this has no significant effect on Erythrocyte Sedimentation Rate (ESR) using Mann-Whitney U Test and no appreciable effect on protein inflammation using Kendall coefficient and no visible effect upon white blood cell inflammation using Independent test. Discussion: The Multimodal 12-session Therapy reduced significantly psychological disorders with chronic diseases, such as tension, health, and its sub-scales, (depression, anxiety, social malfunction and somatic function) while its effects on ESR, protein inflammation and white blood cell inflammation were not discernible.